2019
DOI: 10.1182/bloodadvances.2019000790
|View full text |Cite
|
Sign up to set email alerts
|

Results from a multidisciplinary clinic guided by geriatric assessment before stem cell transplantation in older adults

Abstract: Key Points GA to guide an MDC evaluation to optimize older adult candidates for hematopoietic cellular therapy is feasible and practical. An MDC evaluation for older adults before transplantation holds promise to mitigate transplant-related morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 51 publications
0
46
0
3
Order By: Relevance
“…Artz and colleagues recently reported that in patients with a median age of 67 undergoing hematopoietic stem cell transplantation for blood cancers, GA-driven interventions implemented by a multidisciplinary geriatrics team improved 1-year overall survival in comparison with conducting a GA alone without a multidisciplinary team to manage any detected vulnerabilities. 32 While provocative, a limitation of this non-randomized study was its use of a historical control group for comparison. In our randomized trial of transplant-ineligible patients age ≥ 75 years undergoing geriatric consultation versus standard oncologic care, we did not find evidence of an effect on 1-year overall survival-even in the frail subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Artz and colleagues recently reported that in patients with a median age of 67 undergoing hematopoietic stem cell transplantation for blood cancers, GA-driven interventions implemented by a multidisciplinary geriatrics team improved 1-year overall survival in comparison with conducting a GA alone without a multidisciplinary team to manage any detected vulnerabilities. 32 While provocative, a limitation of this non-randomized study was its use of a historical control group for comparison. In our randomized trial of transplant-ineligible patients age ≥ 75 years undergoing geriatric consultation versus standard oncologic care, we did not find evidence of an effect on 1-year overall survival-even in the frail subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…39 However, these studies are mainly in the context of chimeric antigen receptor T-cell therapies 38,40,41 and bispecific T-cell engagers. 42 CRS is also recognized after haploidentical HCT, particularly when PBSCs are infused as the graft source, [43][44][45] with prognostic implications. 42 CRS in matched donor or MMUD-HCT has not been fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the concept that frailty is dynamic is important given the high degree of symptom burden that often accompanies a diagnosis of a hematologic malignancy as well as the possibility that it may be reversible with intervention and optimization of individual vulnerabilities. 11…”
Section: Concepts Of Geriatrics In the Oncology Clinic: Geriatric Assessment And Frailtymentioning
confidence: 99%